Bio-Inspired Synthesis of Injectable, Self-Healing PAA-Zn-Silk Fibroin-MXene Hydrogel for Multifunctional Wearable Capacitive Strain Sensor - Rongjie Wang; Boming Jin; Jiaxin Li; Jing Li; Jingjing Xie; Pengchao Zhang; Zhengyi Fu (Gels)
Conductive hydrogels have important application prospects in the field of wearable sensing, which can identify various biological signals for human motion monitoring. However, the preparation of flexible conductive hydrogels with high sensitivity and stability to achieve reliable signal recording remains a challenge. Herein, we prepared a conductive hydrogel by introducing conductive Ti3C2Tx MXene nanosheets into a dual network structure formed by Zn2+ crosslinked polyacrylic acid and silk fibroin for use as a wearable capacitive strain sensor. The prepared injectable hydrogel has a uniform porous structure and good flexibility, and the elongation at break can reach 1750%. A large number of ionic coordination bonds and hydrogen bond interactions make the hydrogel exhibit good structural stability and a fast self-healing property (30 s). In addition, the introduction of Ti3C2Tx MXene as a conductive medium in hydrogel improves the conductivity. Due to the high conductivity of 0.16 S/m, the capacitive strain sensor assembled from this hydrogel presents a high gauge factor of 1.78 over a wide strain range of 0–200%, a fast response time of 0.2 s, and good cycling stability. As a wearable sensor, the hydrogel can accurately monitor the activities of different joints in real-time. This work is expected to provide a new approach for wearable hydrogel electronic devices.